2020
DOI: 10.1016/j.joca.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Greater risks of complications, infections, and revisions in the obese versus non-obese total hip arthroplasty population of 2,190,824 patients: a meta-analysis and systematic review

Abstract: Background: Obesity is an epidemic, especially in developed countries. This affects the general health of these patients, especially when they are having a major surgical procedure such as total hip arthroplasty (THA). Several articles have described the effects of obesity on THA with varying conclusions. This metaanalysis aims to compare the outcomes, complications, and peri-operative parameters of THA in the obese (BMI!30 kg/m 2) vs non-obese (BMI<30 kg/m 2) population as well as a subgroup analysis of morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 75 publications
2
38
1
Order By: Relevance
“…Severe obesity is widely associated with reduced cardiopulmonary capacity, metabolic abnormalities and decreased haemostasis, which may predispose patients to morbidity and mortality after surgery. 14 These factors might lead to a higher threshold for orthopaedic surgeon to progress to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Severe obesity is widely associated with reduced cardiopulmonary capacity, metabolic abnormalities and decreased haemostasis, which may predispose patients to morbidity and mortality after surgery. 14 These factors might lead to a higher threshold for orthopaedic surgeon to progress to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Revision surgery was necessary in 8.4% of all patients, with OB patients showing an increased but not statistically significant tendency to require the most revisions. Another investigation involving a large register study showed an increased revision rate for OB patients [ 42 ]. Sayed-Noor et al found higher 2-year and 5-year revision rates for OW and OB patients in primary THA.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized and well recorded that obesity is influencing the rate of peri- and postoperative complications in THA and TKA arthroplasty. There are several meta-analyses, including those by Kunutsor et al 18 and reviews by Liu et al, 19 21 Ponnusamy et al, 22 Boyce et al, 23 Chaudhry et al, 24 and Sun and Li. 25 They all reported that obesity results in increased rates of infections and revisions secondary to deep infection besides an increase in overall complications.…”
Section: Recommendationsmentioning
confidence: 99%
“…Nevertheless, despite the overall increased complication rate in obese THA and TKA patients, patient-relevant outcome improvements (PROMS) are often comparable to those for non-obese patients. 19 , 21 What this means is that although obese patients rarely achieve the high outcome scores that many non-obese reach in terms of function, as they usually start a lower level preoperatively, their overall gain is often comparable to that of non-obese patients. 23 …”
Section: Recommendationsmentioning
confidence: 99%